Convergence of Blockchain, IoT, and AI - Sandner, Philipp; Gross, Jonas; Richter, Robert (Frontiers in Blockchain, 2020)
Blockchain, IoT, and AI are key technologies driving the next wave of the digital transformation. We argue that these technologies will converge and will allow for new business models: Autonomous agents (i.e., sensors, cars, machines, trucks, cameras, and other IoT devices) will in the future act as own profit centers that (1) have a digital twin leveraging IoT, (2) send and receive money leveraging blockchain technology on their own and (3) autonomously make decisions as independent economic agents leveraging AI and data analytics. We further argue that this convergence will drive the development of such autonomous business models and, with it, the digital transformation of industrial corporations.